Latin American Critical Social Sciences and Situated Thinking - Damián Pachón Soto (El Ágora USB)
The article highlights the dangers of conducting research without being aware of the place of enunciation. It reviews the deformation of the American reality by European science in the 17th and 18th centuries. Subsequently, it illustrates with examples the attempts to overcome this problem in the American eighteenth century, a period that gave rise to a marked interest in investigating the American reality, an endeavor that reached its climax with the emergence of the so-called Social Sciences in the mid-twentieth century. Finally, we reflect on some of the implications of situated and localized thinking. René Zavaleta’s concept of variegation is used for this purpose. It is found that thinking and researching situationally, by attending to specific contexts, avoids losing sight of the heterogeneity and complexity of situated realities. It is something that can also contribute to create emancipatory possibilities.